2020
DOI: 10.7554/elife.55957
|View full text |Cite
|
Sign up to set email alerts
|

LUZP1, a novel regulator of primary cilia and the actin cytoskeleton, is a contributing factor in Townes-Brocks Syndrome

Abstract: Primary cilia are sensory organelles crucial for cell signaling during development and organ homeostasis. Cilia arise from centrosomes and their formation and function is governed by numerous factors. Through our studies on Townes-Brocks Syndrome (TBS), a rare disease linked to abnormal cilia formation in human fibroblasts, we uncovered the leucine-zipper protein LUZP1 as an interactor of truncated SALL1, a dominantly-acting protein causing the disease. Using TurboID proximity labeling and pulldowns, we show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 89 publications
(134 reference statements)
2
44
0
Order By: Relevance
“…Another important actin binding protein implicated in ciliogenesis is leucine zipper protein 1 (LUZP1) ( Wang and Nakamura, 2019 ). In cycling cells, LUZP1 localizes to the pericentriolar matrix at the proximal end of each centriole, the actin cytoskeleton and the midbody ( Bozal-Basterra et al, 2020 ). In cell cycle-arrested cells, LUZP1 localizes to the basal body and to the ciliary axoneme.…”
Section: Actin Binding Proteins Ciliogenesis and Cilia Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…Another important actin binding protein implicated in ciliogenesis is leucine zipper protein 1 (LUZP1) ( Wang and Nakamura, 2019 ). In cycling cells, LUZP1 localizes to the pericentriolar matrix at the proximal end of each centriole, the actin cytoskeleton and the midbody ( Bozal-Basterra et al, 2020 ). In cell cycle-arrested cells, LUZP1 localizes to the basal body and to the ciliary axoneme.…”
Section: Actin Binding Proteins Ciliogenesis and Cilia Maintenancementioning
confidence: 99%
“…However, truncated mutant forms of SALL1 that cause TBS1 appear to interact with LUZP1 ( Bozal-Basterra et al, 2018 ). This interaction causes LUZP1 degradation through the ubiquitin proteasome system, since inhibition of the proteasome in TBS1 cells lead to accumulation of LUZP1 ( Bozal-Basterra et al, 2020 ). Loss of LUZP1 results in reduced actin polymerization, increased cilia incidence and length, and increased Shh signaling ( Bozal-Basterra et al, 2020 ; Gonçalves et al, 2020 ).…”
Section: Actin Binding Proteins Ciliogenesis and Cilia Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some authors proposed the involvement of SALL1 in the regulation of higher-order chromatin structures and hypothesized that the protein may be a component of a distinct heterochromatin-dependent silencing process [ 10 , 11 ]. Recently, studies have found that SALL1 can interact with ciliogenesis suppressors CCP110 and CEP97 and mutations in SALL1 may disrupt the formation and function of cilia [ 1 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some authors proposed the involvement of SALL1 in the regulation of higher-order chromatin structures and hypothesized that the protein may be a component of a distinct heterochromatin-dependent silencing process [10,11]. Recently, studies have found that SALL1 can interact with ciliogenesis suppressors CCP110 and CEP97 and mutations in SALL1 may disrupt the formation and function of cilia [1,12].…”
Section: Introductionmentioning
confidence: 99%